¿Qué hemos de saber y saber hacer los profesores de ciencias? - Gil Pérez, D. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This work was aimed at synthesizing the scientific knowledge and skills required as determined by experience on science teaching research.